The effect of different liquids on the surface roughness and color stability of single shade and nanohybrid resin composites: An AFM and SEM analysis - Ipek, Irem; Bilge, Kubra (Wiley, 2024)
The aim of this study is to evaluate the surface roughness (SR) and color changes of single-shade and nanohybrid resin-based restorative materials (RBC) after immersion in liquids at different pH values. For RBCs, a total of 120 specimens, 30 for each material, were prepared using 10 mm diameter and 2 mm thick molds. For flowable bulk fill RBC, a total of 40 specimens, 10 for each material, were prepared using 10 mm diameter and 4 mm thick molds (n = 10). After initial color and SR measurements, samples were stored in the liquids for 14 days and all of the measurements were repeated on 14th days. Scanning electron microscopy and atomic force microscopy analyzes were performed in all groups. When SR results are examined; among all liquids, the highest SR value was observed in the Carisma Diamond One (CDO) group, while the lowest SR value was observed in the Omnichroma Flow Bulk (OMF) group (p < .05). When the color changes (Delta E) results are examined; it was observed that CDO group had highest color change and OMF group had the lowest values. It has been observed that among the liquids, the liquids that affect the Delta E values of the materials the most are coffee and cola. When the Delta E values of the subgroups of the materials were examined, there was a statistically significant difference in all subgroups of RBCs (p < .05). While acidic liquids increased the SR of RBCs, coffee more affected the color change of RBCs.
Keywords: AFM; color stability; SEM; single-shade composite resin; surface roughness